Analysis Of Mercury (Hg) In Mujair Fish (Oreochromis mosambicus) In Limboto Lake, Gorontalo Province - Tuli, Munirah; Panigoro, Citra F; Tanipu, Funco; Walangadi, Novianti (Journal of Aquaculture and Fish Health, 2024)
The occurrence of silting of the lake and sedimentation in Limboto Lake has become a place for the deposition of heavy metals, especially mercury. In recent years it has been known that the water of Lake Limboto has been polluted by mercury based on data from the Agency for the Environment, Research and Technology (Balihristi), Gorontalo Province in 2007.This study aims to analyze the mercury (Hg) content of mujair fish (Oreochromis mossambicus) in Limboto Lake. This research was conducted in November 2018- June 2019. The method used in this research is descriptive method. Sampling of water and fish was carried out by purposive sampling by dividing the research location into 2 stations, namely Station I in the floating net cages  and Station II outside the KJA Measurement of mercury content (Hg) was carried out at the Laboratory of Fisheries Product Quality Development and Testing (LPPMHP) Gorontalo City using the Atomic Absorbtin Spectrophotometer (AAS). From the results of the study, it was found that,  the Mercury (Hg) Content in Lake Limboto Waters,  Stasion I was 0.0014 ppm and Station II was 0.0007 ppm, and for mujair fish organs the highest was in meat, namely outside KJA 0.0037 ppm and in meat, the lowest was in KJA 0.0035 ppm.. Nakoe et al. (2014) examined the risk of exposure to mercury (Hg) in humans who consume Mujair (Oreochromis niloticus) from Lake Limboto using the Limboto approach. Limboto using an environmental health analysis approach with a variable test method of body weight, consumption level and frequency. Concentration mercury levels of tilapia in Lake Limboto are between 0.007 - 0.089 mg/kg while the mercury levels in the lake are between 0.0014 mg/L. lake is around 0.0014 mg/L.